Legal Implications of Constitutional Court Decision Number 46/PUU-VIII/2010 on Inheritance Rights of Children Born Out of Wedlock - Suparidho, Febrihadi; Muhammad, Ade Sultan; Daulay, R. Fahmi Natigor (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to determine the legal implications of the Constitutional Court Decision Number 46/PUU-VIII/2010 on the inheritance rights of illegitimate children. In the Indonesian legal system, referring to Law Number 1 of 1974 concerning Marriage, it states that illegitimate children only have a civil relationship with their mother, so they are not entitled to inheritance from their father. However, the Constitutional Court's decision changed this paradigm by recognizing the civil relationship of illegitimate children with their biological father if it can be proven scientifically and technologically, such as through DNA testing. This study uses a normative legal research method with primary and secondary legal materials. The results of the study indicate that the legal implications of the Constitutional Court's Decision provide fairer and more equal legal protection for illegitimate children in obtaining recognition of inheritance rights from their father which can be proven scientifically from the science and technology recognized by applicable law.